Modification of 2fn-Recuv Test Bench - Amran, Haziq; Yaakub, Mohd Fauzi (Progress in Aerospace and Aviation Technology, 2024)
The objective of this study is to modify the 2fn-recuv test bench. The test bench is used to carry out drone flight simulations. It can provide a controlled environment to ensure the drone’s safety. The test bench allows precise data collection and analysis for an unmanned aerial vehicle (UAV). First, a literature review is conducted to understand and analyse the design of the previous test bench. The limitations of CNC machines are also being studied to ensure the modified design can be fabricated. Based on the findings and results, a 3D drawing is created, taking into account the need for machining. The first prototype is made using a 3D printer. It allows for initial testing and checking for possible failures of the design. The completed part of the prototype is then fabricated using a CNC machine. The new test bench is made of aluminium to give it more rigidity and strength. Stress analysis is done using Solidworks 2020 to ensure the test bench can withstand the weight of the drone. The test bench is tested using Labview to record the angle of each movement of the drone, such as pitch, roll, and yaw. The maximum and minimum values indicate the angle of the test bench for the drone’s flight simulation.